Monolithic Flexible Supercapacitors Integrated into Single Sheets of Paper and Membrane via Vapor Printing. Issue 19 (10th March 2017) - Liu, Andong; Kovacik, Peter; Peard, Nolan; Tian, Wenda; Goktas, Hilal; Lau, Jonathan; Dunn, Bruce; Gleason, Karen K.
Abstract : A novel approach to fabricate supercapacitors (SCs) via vapor printing, specifically oxidative chemical vapor deposition (oCVD), is demonstrated. Compared to stacking multiple layers into a SC, this method enables the monolithic integration of all components into a single‐sheet substrate, minimizing the inactive materials and eliminating the possibility of multilayer delamination. Electrodes comprised of pseudocapacitive material, poly(3, 4‐ethylenedioxythiophene) (PEDOT), are deposited into both sides of a sheet of flexible porous substrate. The film deposition and patterning are achieved in a single step. The oCVD PEDOT penetrates partially into the porous substrate from both surfaces, while leaving the interior of the substrate serving as a separator. Near the surface, the PEDOT coating conforms to the substrate's structure without blocking the pores, resembling the substrate's intrinsic morphology with high surface area. The porously structured PEDOT coating, paired with in situ ion gel electrolyte synthesis, gives enhanced electrode–electrolyte interfaces. The monolithic device demonstrates high volumetric capacitance (11.3 F cm −3 ), energy density (2.98 mWh cm −3 ), and power density (0.42 W cm −3 ). These outstanding performance metrics are attributed to the large loading of active materials, minimization of inactive materials, and good electrode–electrolyte interfaces. SC arrays can be printed on a single substrate without the use of wire interconnects. Abstract : A monolithically integrated supercapacitor is demonstrated to give high energy and power densities while avoiding delamination when being flexed. It relies on vapor‐deposited poly(3, 4‐ethylenedioxythiophene) electrodes that penetrate partially into both sides of a paper/membrane substrate, leaving the substrate's interior as separator. The electrodes conform to the substrate's outer texture, resulting in their large surface area for fast ion transport.